Comparison Between Prophylactic use of Atropine and Glycopyrolate in Prevention of Spinal Induced Hypotension in Patients Undergoing C-Section - Laila Khalid, Khawar Aziz, Aqil Qayoom, Muhammad Sirajuddin, Ali Asghar, Ayesha Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study is to compare the efficacy of atropine and glycopyrrolate in reducing the risk of hypotension caused by spinal anesthesia in patients undergoing caesarean sections. Methods: After ethical approval from institution review board, this randomized control was carried out at Liaqat national hospital and medical college. 332 pregnant women in a row who had chosen to have a caesarean section were enlisted through non-probability consecutive sampling technique. Subjects were randomly assigned to one of two groups of 166 using computer-generated randomization tables. Group A Patients received intravenous atropine in dose of 0.01mg/kg before inducing spinal anesthesia. Group B Patients received intravenous glycopyrrolate in dose of 0.01mg/kg before inducing spinal anesthesia. Pre-surgical, operational, and post-operative treatment for all patients was adhered to the same established protocols. Results: The mean age of the participants in both study groups were 26.28±4.03 and 26.07±3.78 years. The mean weight of the participants in both study groups were 75.24±7.6 and 74.17±7.54 Kg. The mean gestation age of the participants in both study groups were 38.82±1.17 and 38.70±1.19 months. The heart rate (HR) 15-minutes after the administration of atropine in group A was 94.89±11.8, and in Group B after administration of glycopyrrolate was 98.18±11.5. A significant difference (P=0.045) in the mean HR of the participants in both study groups was observed. The Mean Arterial Pressure (MAP) 15-minutes after the administration of atropine in group A was 76.63±7.9, and in Group B after administration of glycopyrrolate was 79.6±10.5. A significant difference (P=0. 0.029) in the mean MAP of the participants in both study groups was observed. Conclusion: Glycopylorate, atropine, spinal anesthesia, hypotension, heart rate